2014
DOI: 10.1002/jib.144
|View full text |Cite
|
Sign up to set email alerts
|

Quality of pilsner malt and roasted malt during storage

Abstract: Malt is usually expected to be stable during 12 months of storage. However, in practice many brewers notice changes in malt aroma during storage. The oxidative stabilities of pilsner malt and roasted malt were evaluated during a 12 month storage at different temperatures (10 and 20°C) and water activities (0.231 and 0.432). The radical content in malt kernels was measured by electron spin resonance spectroscopy and the volatile profile of the resulting sweet worts was measured by head-space analysis followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
(36 reference statements)
1
10
0
Order By: Relevance
“…Dark beer induced a pro‐oxidative effect, determined by ESR spectroscopy using spin trapping, reducing the oxidative stability of lager beer and resulting in shorter lag phases for radical formation and increased rates of oxidative reactions (Nøddekær and Andersen ). Accordingly, roasted malt was much more unstable than Pilsener malt and exhibited higher radical intensity by ESR, with a negative effect on the oxidative stability of wort and beer caused by increased radical formation (Hoff and others ). Dark worts were found to be less stable with high radical intensities and high iron content, contrary to light worts that were less reactive toward oxidation with low radical intensity and low iron content.…”
Section: Pro‐oxidant Potential Of Maltmentioning
confidence: 99%
“…Dark beer induced a pro‐oxidative effect, determined by ESR spectroscopy using spin trapping, reducing the oxidative stability of lager beer and resulting in shorter lag phases for radical formation and increased rates of oxidative reactions (Nøddekær and Andersen ). Accordingly, roasted malt was much more unstable than Pilsener malt and exhibited higher radical intensity by ESR, with a negative effect on the oxidative stability of wort and beer caused by increased radical formation (Hoff and others ). Dark worts were found to be less stable with high radical intensities and high iron content, contrary to light worts that were less reactive toward oxidation with low radical intensity and low iron content.…”
Section: Pro‐oxidant Potential Of Maltmentioning
confidence: 99%
“…During the short-term maturing of malt, an adequate hydration of its colloidal substances takes place and subsequent activation of amylolytic enzymes is likely responsible for a slight increase in diastatic power (Basařová, 2015;Kieninger and Narziss 1975). On the contrary, the research carried out by Hoff et al (2014) showed that during malt storage, the sugar content remains on the same level, showing that the major malt components and activities of starch degrading enzymes are almost intact. There was a small, statistically insignificant decrease in diastatic power within the experiment, which is in agreement with the results of experiments conducted by Fleurat-Lessard et al (2005b).…”
Section: Amylolytic Modificationmentioning
confidence: 93%
“…Moreover, the main yeast metabolites arise from diverse chemical families, such as acids, alcohols, esters, monoterpenic compounds, norisoprenoids, sesquiterpenic compounds, sulfur compounds, and volatile phenols [4,5]. Furthermore, chemical changes, which may occur in raw materials' storage [6,7] and throughout the brewing process, as well as the phenomena of beer aging [8] may promote changes in the beer's volatile composition. Schematic representation proposed to explain sources of the target analytes under study (acids, alcohols, esters, monoterpenic compounds, norisoprenoids, sesquiterpenic compounds, sulfur compounds, and volatile phenols), taking into account that they can be formed from raw materials and/or produced and biotransformed along brewing, also the main associated metabolic pathways were highlighted (magnifying glass) [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the main yeast metabolites arise from diverse chemical families, such as acids, alcohols, esters, monoterpenic compounds, norisoprenoids, sesquiterpenic compounds, sulfur compounds, and volatile phenols [ 4 , 5 ]. Furthermore, chemical changes, which may occur in raw materials’ storage [ 6 , 7 ] and throughout the brewing process, as well as the phenomena of beer aging [ 8 ] may promote changes in the beer’s volatile composition.…”
Section: Introductionmentioning
confidence: 99%